2020
DOI: 10.3892/etm.2020.8451
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-T-lymphocyte globulin-Fresenius as an induction agent in deceased-donor renal transplantation: A cohort study

Abstract: Anti-T-lymphocyte globulin (ATG) is frequently used in the induction regimen of renal transplantation, but its dose has not been standardized. In the present study, the efficacy of different ATG-Fresenius (ATG-F) doses was assessed in recipients of renal transplantation. A total of 131 adult recipients of renal transplantation who received ATG-F induction between August 2015 and July 2018 were included. The incidence of biopsy-confirmed acute rejection, graft function, as well as graft and patient survival wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…High tacrolimus trough levels have been associated with a high incidence of new‐onset diabetes in the first year after transplantation, 20 while reduced tacrolimus trough levels in the first 3 months after transplantation were found to lower the prevalence of NODAT 21 . In the present study, the incidence of NODAT during the first year (12.7%) was lower than the incidence rates reported in most international studies, 22 possibly because our center aims to maintain optimal tacrolimus cutoff levels during the early post‐transplantation period depending on the level of immunological risk 23 . However, the precise cutoff value of tacrolimus trough levels that is associated with the risk of NODAT is yet to be determined.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…High tacrolimus trough levels have been associated with a high incidence of new‐onset diabetes in the first year after transplantation, 20 while reduced tacrolimus trough levels in the first 3 months after transplantation were found to lower the prevalence of NODAT 21 . In the present study, the incidence of NODAT during the first year (12.7%) was lower than the incidence rates reported in most international studies, 22 possibly because our center aims to maintain optimal tacrolimus cutoff levels during the early post‐transplantation period depending on the level of immunological risk 23 . However, the precise cutoff value of tacrolimus trough levels that is associated with the risk of NODAT is yet to be determined.…”
Section: Discussioncontrasting
confidence: 62%
“… 21 In the present study, the incidence of NODAT during the first year (12.7%) was lower than the incidence rates reported in most international studies, 22 possibly because our center aims to maintain optimal tacrolimus cutoff levels during the early post‐transplantation period depending on the level of immunological risk. 23 However, the precise cutoff value of tacrolimus trough levels that is associated with the risk of NODAT is yet to be determined. Maes et al 24 found that patients with high tacrolimus trough levels (>15 ng/mL) during the first month after transplantation were at risk for the development of NODAT, while Rodrigo et al 19 considered that NODAT was prone to develop during the first year after transplantation when the tacrolimus trough level exceeded 20 ng/mL in the early post‐transplantation period.…”
Section: Discussionmentioning
confidence: 99%
“…Her platelet count was low till 'Day 30'. Anaemia, leukopenia and thrombocytopenia were commonly observed adverse reactions to administration of rATG, found in other studies [18]. The hematological side effects may be aggravated by mycophenolate mofetil and Having thrombocytopenia in this patient delayed the timing of graft biopsy; it can be done only on 'Day 7' after correction with platelet transfusion.…”
Section: Discussionmentioning
confidence: 49%
“…ATG-F was administered as described previously. 11 Maintenance therapy with oral tacrolimus, MPA, corticosteroids, and prophylaxis for P. jiroveci and cytomegalovirus (CMV) also was administered as described previously. 11 …”
Section: Methodsmentioning
confidence: 99%